Improving Data Quality in Face-to-Face Survey Research. Issue 1 (January 2020) - Logan, Carolyn; Parás, Pablo; Robbins, Michael; Zechmeister, Elizabeth J.
ABSTRACT: Data quality in survey research remains a paramount concern for those studying mass political behavior. Because surveys are conducted in increasingly diverse contexts around the world, ensuring that best practices are followed becomes ever more important to the field of political science. Bringing together insights from surveys conducted in more than 80 countries worldwide, this article highlights common challenges faced in survey research and outlines steps that researchers can take to improve the quality of survey data. Importantly, the article demonstrates that with the investment of the necessary time and resources, it is possible to carry out high-quality survey research even in challenging environments in which survey research is not well established.